Effects of Insect-Proof Net Cultivation, Rice-Duck Farming, and Organic Matter Return on Rice Dry Matter Accumulation and Nitrogen Utilization - Liu, Xin; Xu, Guochun; Wang, Qiangsheng; Hang, Yuhao (Frontiers in Plant Science, 2017)
Insect-proof net cultivation (IPN), rice-duck farming (RD) and organic matter return (OM) are important methods to realize sustainable development of rice production. A split-plot field experiment was performed to study the effects of IPN, RD and OM on the rice yield, dry matter accumulation and N utilization. Results showed that compared to inorganic N fertilizer (IN), wheat straw return (WS) and biogas residue return (BR) increased the rice yield by 2.11–4.28% and 4.78–7.67%, respectively, and also improved dry matter and N accumulation after the elongation stage (EG), dry matter and N translocation, and N recovery efficiency (NRE). These results attributed to an increase in leaf SPAD values and net photosynthetic rate (Pn) after the EG. Compared to conventional rice farming (CR), RD promoted the rice yield by 1.52–3.74%, and contributed to higher the leaf photosynthesis, dry matter and N accumulation, dry matter and N translocation, and NRE. IPN decreased the intensity of sun radiation in the nets due to the coverage of the insect-proof nets, which declined the leaf Pn, dry matter accumulation and translocation, N absorption and translocation, and NRE compared to open field cultivation (OFC). The rice yield of IPN were 2.48–4.98% lower than that of OFC. Compared to the interaction between CR and IN, the interaction between RD and OM improved the rice yield by 5.26–9.33%, and increased dry matter and N accumulation after the EG, dry matter and N translocation, and NRE. These results indicated that OM, RD and the interaction between RD and OM could promote dry matter accumulation and N utilization, which was beneficial to improve the rice yield.